Loss of the Alox5 gene impairs leukemia stem cells and prevents chronic myeloid leukemia - Chen, Yaoyu (2009)
Targeting of cancer stem cells is believed to be essential for curative therapy of cancers, but supporting evidence is limited. Few selective target genes in cancer stem cells have been identified. Here we identify the arachidonate 5-lipoxygenase (5-LO) gene (Alox5) as a critical regulator for leukemia stem cells (LSCs) in BCR-ABL-induced chronic myeloid leukemia (CML). In the absence of Alox5, BCR-ABL failed to induce CML in mice. This Alox5 deficiency caused impairment of the function of LSCs but not normal hematopoietic stem cells (HSCs) through affecting differentiation, cell division, and survival of long-term LSCs (LT-LSCs), consequently causing a depletion of LSCs and a failure of CML development. Treatment of CML mice with a 5-LO inhibitor also impaired the function of LSCs similarly by affecting LT-LSCs, and prolonged survival. These results demonstrate that a specific target gene can be found in cancer stem cells and its inhibition can completely inhibit the function of these stem cells.